Simple mechanism rules the dynamics of volleyball - Chacoma, Andrés Alberto (2022)
In volleyball games, we define a rally as the succession of events observed since the ball is served until one of the two teams on the court scores the point. In this process, athletes evolve in response to physical and information constraints, spanning several spatiotemporal scales and interplaying co-adaptively with the environment. Aiming to study the emergence of complexity in this system, we carried out a study focused on three steps: data collection, data analysis, and modeling. First, we collected data from 20 high-level professional volleyball games. Then we conducted a data-driven analysis from where we identified fundamental insights that we used to define a parsimonious stochastic model for the dynamics of the game. On these bases, we show that it is possible to give a closed-form expression for the probability that the players perform n hits in a rally using only two stochastic variables. Our results fully agree with the empirical observations and represent a new advance in the comprehension of team-sports competition complexity and dynamics.